2014
DOI: 10.1002/ajpa.22593
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and interspecific variation in macaque molar enamel thickness

Abstract: Enamel thickness has played an important role in studies of primate taxonomy, phylogeny, and functional morphology, although its variation among hominins is poorly understood. Macaques parallel hominins in their widespread geographic distribution, relative range of body sizes, and radiation during the last five million years. To explore enamel thickness variation, we quantified average and relative enamel thickness (AET and RET) in Macaca arctoides, Macaca fascicularis, Macaca fuscata, Macaca mulatta, Macaca n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 88 publications
1
23
0
Order By: Relevance
“…For example, Kato et al (2014) assessed intra-and interspecific variation in macaque molar enamel thickness -a genus with a wide geographic range that exploits a diversity of habitats that the authors highlight as analogous to hominids. Enamel thickness measurements for 386 molars representing six species yielded no sexual dimorphism in AET or RET.…”
Section: Enamel Thickness Variationmentioning
confidence: 99%
“…For example, Kato et al (2014) assessed intra-and interspecific variation in macaque molar enamel thickness -a genus with a wide geographic range that exploits a diversity of habitats that the authors highlight as analogous to hominids. Enamel thickness measurements for 386 molars representing six species yielded no sexual dimorphism in AET or RET.…”
Section: Enamel Thickness Variationmentioning
confidence: 99%
“…This is supported by microwear analyses that suggest a closer fit with Papio ursinus (DeMiguel et al, 2014;L'Engle Williams, 2013;Smith and Williams, 2010;Ungar, 1996). Accordingly, similarly to the variation in molar enamel thickness seen in macaques (Kato et al, 2014), the intermediate-thick (Martin, 1985) enamel of Oreopithecus could reflect wider dietary diversity implying the interaction with a greater range of food material properties than previously thought.…”
Section: Tooth Morphostructurementioning
confidence: 72%
“…However, even if molar enamel thickness does not seem to behave as sexually dimorphic (e.g., Hlusko, 2016;Hlusko et al, 2004;Rossi et al, 1999), a growing body of evidence indicates a considerable amount of interspecific temporal and geographic variation (e.g., Kato et al, 2014;Smith et al, 2011Smith et al, , 2012. Conversely, the extent of intraspecific variation ranges in most cases from poorly reported to simply unknown, and even in extant humans enamel thickness chrono-geographic variation is far from being appropriately documented and, with very few exceptions (e.g., Feeney et al, 2010;Grine, 2005), most currently available information is limited to European or European-derived population samples (rev.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence exists for lifetime-related enamel thickness and dietary wear association in extant primates (e.g., Pampush et al, 2013) and positive selection for adaptation in human evolution has been shown for the genes coding for the enamel matrix proteins (e.g., Daubert et al, 2016;Horvath et al, 2014). However, given also the high phenotypic plasticity of enamel thickness (e.g., Hlusko, 2016;Kato et al, 2014;Smith et al, 2012), it is possible that a fraction of the signal provided by any kind of tooth enamel "diphyodontic index" is non-adaptive, or that the degree of adaptability and functional significance of this trait varies topographically across the dentition. With this respect, together with some methodological advancement in the identification of the most reliable parameters and tooth crown areas to be considered for intertaxonomic investigations, a fruitful area of research would be to test the congruence of the "diphyodontic signal" between the anterior and the postcanine dentition, as well as between enamel and the enamel-dentine junction topography.…”
Section: Discussionmentioning
confidence: 99%